THE PROTECTION FOR CONSUMERS OF DENTAL PROSTHESIS CARE - Revita Dwi Cahyani; Gianto Al Imron (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study examines about the legal protection for consumers of dental prosthestis care. The aim of this study is to reveal fundamentally how the liability of dental artisans for consumers who experience disadvanatge in using the services of that dental artisans. The researcher uses legal research method. The result of this study shows that the Government through the Ministry of Health has regulated the dental prosthesis care into the Regulation of the Minister of Health No. 39.2014. Meanwhile, if there is a detrimental violation to the consumer, hence, this dental artisan will be sentenced through Article 62 section (1) of the consumer protection act (UUPK). And if the dental service business does not have a permission, it will be subjected to a criminal penalty in accordance with Article 78 of the Medical Practice Act. The supervision of the dental artisans practice in Indonesia does not seem strict although this practice is a health practice which has a high risk of malpractice to the patients.